2005
DOI: 10.1210/me.2004-0302
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Progesterone Levels during Pregnancy and Parturition by Signal Transducer and Activator of Transcription 5 and 20α-Hydroxysteroid Dehydrogenase

Abstract: The two highly related signal transducers and activators of transcription (Stats), Stat5a and Stat5b, are major mediators of prolactin signaling in both the mammary gland and in the ovary. Deficiencies in Stat5b, or in both Stat5a and Stat5b, result in loss of pregnancy during midgestation and are correlated with an increase in ovarian 20alpha-hydroxysteroid dehydrogenase (20alpha-HSD) and a decrease in serum progesterone, which normally declines only immediately before parturition. To determine the relative c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
112
1
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 128 publications
(120 citation statements)
references
References 44 publications
6
112
1
1
Order By: Relevance
“…The AKR1C2 is also known as the bile acid binding protein because one of its functions may be to transport bile acids from the canalicular to the polar end of hepatocyte (Stolz et al, 1993). AKR1C1 which possesses 20α-HSD activity, has been suggested to play an important role in reductive inactivation of progesterone into 20α-hydroxyprogesterone and deficiency of this enzyme has been shown to cause a delay in parturition (Piekorz et al, 2005). Although much is known about the substrate specificity and tissue distribution of AKR1C enzymes, their physiological roles still remains elusive.…”
Section: Akr1c1-c4 -Hydroxysteroid Dehydrogenasesmentioning
confidence: 99%
See 1 more Smart Citation
“…The AKR1C2 is also known as the bile acid binding protein because one of its functions may be to transport bile acids from the canalicular to the polar end of hepatocyte (Stolz et al, 1993). AKR1C1 which possesses 20α-HSD activity, has been suggested to play an important role in reductive inactivation of progesterone into 20α-hydroxyprogesterone and deficiency of this enzyme has been shown to cause a delay in parturition (Piekorz et al, 2005). Although much is known about the substrate specificity and tissue distribution of AKR1C enzymes, their physiological roles still remains elusive.…”
Section: Akr1c1-c4 -Hydroxysteroid Dehydrogenasesmentioning
confidence: 99%
“…Hence, it is difficult to draw direct parallels between human and murine enzymes. To date, only one knockout model of the enzyme of this family, namely 20α-HSD, has been reported, and this led to a decrease in the survival of pups and an increase in the duration of the estrous cycles and pregnancy (Ishida et al, 2007;Piekorz et al, 2005). Development of specific inhibitors and fluorogenic substrates that can be used to interrogate the role of individual AKR1C isoforms, as well as serve as potential drug candidates is under way (Byrns et al, 2008;Bauman et al, 2005;Yee et al, 2006).…”
Section: Akr1c1-c4 -Hydroxysteroid Dehydrogenasesmentioning
confidence: 99%
“…It is well known that the activity of 20aHSD rises at the end of pregnancy and that PRL represses its expression (Albarracin et al 1994). The key role of 20aHSD as a critical component of luteolysis at the end of pregnancy was evidenced most strikingly by the development of the 20aHSD knockout mouse, in which circulating P 4 levels remain elevated and parturition is significantly delayed (Piekorz et al 2005). PGF2a, after binding to its receptor, acts through a cascade of signaling events involving hormones, cytokines, and possible disruptions of intracellular growth factor signaling (Orlicky et al 1992, Olofsson et al 1996.…”
Section: Introductionmentioning
confidence: 99%
“…Piekorz et al [10] recently reported that the parturition of mice lacking the 20α-HSD gene is delayed by 2-3 days and that the pups of these mice die in utero. In their study, the progesterone levels at term of pregnancy were 3-4 times higher than those in wild-type mice.…”
Section: Discussionmentioning
confidence: 99%
“…PGF 2 α -receptor knockout (FP -/-) mice failed to deliver pups due to lack of decline of serum progesterone levels at parturition [9]; at that time, no elevation of 20α-HSD activity was observed [8]. Furthermore, it has recently been reported that 20α-HSD -/-mice exhibited a phenotype similar to FP -/-mice at parturition; notably, the fetuses of the latter mice all died in utero [10]. Thus, expression of 20α-HSD appears to be closely related to functional luteolysis in rodent reproduction.…”
mentioning
confidence: 99%